Pembangunan Website Pengelolaan Kegiatan Komunitas menggunakan Framework CodeIgniter (Studi Kasus: Komunitas Generasi Baru Indonesia Malang) - Nur Afifah; Denny Sagita Rusdianto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Generasi Baru Indonesia(GenBI) Malang is a community of Bank Indonesia scholarship recipients which participate in holding social activities. Procurement of social activities in GenBI Malang implements an activity management process consists of planning, organizing, implementing, and controlling(monitoring and evaluating). The process of planning until implementing produces activities documents kept by the activity committee consequently causing executive boards need more time and effort to collect and make a report that is used by community advisor to evaluate activities. Besides, there is no log recording of activity management details which makes monitoring process not being carried out comprehensively but only on the activity document. These problems can be resolved by developing a community activities management website. The website system allows data access wherever and whenever. The system has features to make activities, submit activities documents, and change activities information wherein details of activity management always recorded so that the system can be the center of activity management. The results of requirement engineering and system design produce 7 actors, 57 functional requirements, 1 non-functional requirement, and 22 database entities. The website based system is implemented using the CodeIgniter framework and MySQL database. The system that was built has been tested at the unit, integration, and validation stages. Compatibility testing also performed with results 100% system content and functionality works.